(untitled) (Revista de Biología Marina y Oceanografía, 2022)
Ophichthid eel genus Aplatophis includes two species restricted to the New World, one distributed in the western Atlantic (A. chauliodus) and the other in the tropical eastern Pacific (A. zorro). Aplatophis zorro is a little-known species that was described in Panama, Gulf of San Miguel, from the collection of a single mature male. This work constitutes the first record of the species in Colombian waters and extends its geographical distribution to more than 483 km south on the American continent. In addition, some morphometric variation of the species, which was only known from the Panamanian holotype, is provided.